Bank margins and profits in a world of negative rates - Molyneux, Philip; Reghezza, Alessio; Xie, Ru (Journal of Banking & Finance, 2019)
By investigating the influence of negative interest rate policy (NIRP) on bank margins and profitability, this paper identifies country- and bank- specific characteristics that amplify or weaken the effect of NIRP on bank performance. Using a dataset comprising 7,359 banks from 33 OECD member countries over 2012–16 and a difference-in-differences methodology, we find that bank margins and profits fell in NIRP-adopter countries compared to countries that did not adopt the policy. Moreover, this adverse NIRP effect depends on bank specific-characteristics such as size, funding structure, business models, assets repricing and product – line specialization. The effectiveness of the pass-through mechanism of NIRP can also be affected by the characteristics of a country's banking system, namely, the level of competition and the prevalence of fixed/floating lending rates.